Therapeutic Potential of N-Acetylcysteine for Wound Healing, Acute Bronchiolitis, and Congenital Heart Defects - Almatar, Manaf; Batool, Tahira; Makky, Essam A. (Bentham Science, 2016)
Wound healing is a composite and vital process in which devitalized tissue layers and cellular structures repair themselves. Bronchiolitis is generally prompted by respiratory syncytial virus or human metapneumovirus; this condition is an acute inflammatory injury of bronchioles. Heart problems that develop before birth are known as congenital heart defects (CHDs), and pregestational diabetes is considered a major predisposing factor of CHDs. N-Acetylcysteine (NAC) is a transformed kind of amino acid cysteine which restores the intracellular levels of the natural antioxidant glutathione when taken internally, thereby assisting the cells’ ability to diminish the damaging effects of reactive oxygen species (ROS).